1998
DOI: 10.1148/radiology.207.1.9530302
|View full text |Cite
|
Sign up to set email alerts
|

Posterior lobe of the pituitary gland: correlation between signal intensity on T1-weighted MR images and vasopressin concentration.

Abstract: The signal intensity ratio on T1-weighted MR images may be used as an indicator for the quantitative evaluation of the vasopressin content in the posterior lobe. The results strongly suggest that the origin of the high signal intensity in the posterior lobe on T1-weighted MR images is the vasopressin-neurophysin II-copeptin complex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(50 citation statements)
references
References 0 publications
3
45
0
2
Order By: Relevance
“…If urine osmolality reaches more than 750 mOsm, either CDI or PP is the diagnosis; the latter two may be distinguished by urine concentrating ability in response to dehydration which is normal in patients with PP [3,38]. MRI can aid in the diagnosis of DI; patients with the characteristic bright spot in the sella turcica are unlikely to have CDI (see above) [3,39,114]. Some difficulties may arise differentiating between NDI, CDI and PP, in that the latter may present with lower than expected concentration capacity, due to medullary washout caused by the massive amount of flow, leading to lack of a concentration gradient.…”
Section: Differential Diagnosis Of Diabetes Insipidusmentioning
confidence: 99%
“…If urine osmolality reaches more than 750 mOsm, either CDI or PP is the diagnosis; the latter two may be distinguished by urine concentrating ability in response to dehydration which is normal in patients with PP [3,38]. MRI can aid in the diagnosis of DI; patients with the characteristic bright spot in the sella turcica are unlikely to have CDI (see above) [3,39,114]. Some difficulties may arise differentiating between NDI, CDI and PP, in that the latter may present with lower than expected concentration capacity, due to medullary washout caused by the massive amount of flow, leading to lack of a concentration gradient.…”
Section: Differential Diagnosis Of Diabetes Insipidusmentioning
confidence: 99%
“…In addition, the posterior lobe may be distorted by the high vertical pressure. Reports using rabbits showed that the high SI in the posterior lobe on T1-weighted MR images is associated with the density of secretory granules containing arginine vasopressin (AVP) [15,16]. In humans, the pituitary posterior lobe shows higher signal intensity than the anterior lobe on T1-weighted MR images from 2 months after birth [23].…”
Section: Discussionmentioning
confidence: 99%
“…Comparison of the SI ratios of the pituitary posterior lobe between the PDH and control groups demonstrated that the PDH group had a significantly lower SI ratio. We speculate that this significantly lower SI ratio in the PDH group was associated with either a deficit in the axonal transport of AVP produced in the hypothalamus to the pituitary posterior lobe or continuous secretion of AVP from the posterior lobe in response to the high osmolarity due to polyuria [1,15,20]. The decrease of SI of the posterior lobe may be a diagnostic marker of PDH dogs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The high intensity in posterior pituitary in T1-weighted MRI images, which reportedly reflects the stock of pituitary AVP, 28 decreased under chronically dehydrated conditions, 29) the lack of the high signal in T1-weighted pituitary MRI images is not specific to CDI. Pituitary MRI is also useful for the differential diagnosis of primary and secondary CDI.…”
Section: Diagnosismentioning
confidence: 99%